2002
DOI: 10.1046/j.1528-1157.2002.19498.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Abnormalities and Epilepsy: A Review for Clinicians and Gene Hunters

Abstract: Summary:Purpose: We analyzed databases on chromosomal anomalies and epilepsy to identify chromosomal regions where abnormalities are associated with clinically recognizable epilepsy syndromes. The expectation was that these regions could then be offered as targets in the search for epilepsy genes.Methods: The cytogenetic program of the Oxford Medical Database, and the PubMed database were used to identify chromosomal aberrations associated with seizures and/or EEG abnormalities. The literature on selected smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
105
0
7

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(122 citation statements)
references
References 184 publications
(194 reference statements)
2
105
0
7
Order By: Relevance
“…14,15 In cases of chromosomal abnormalities, the characteristics of epilepsy are considered to be non-specific, difficult to classify according to the International Classification of Epilepsy, 15 and often resistant to treatment. 16,17 However, some chromosomal abnormalities, such as ring 20 syndrome 18,19 and Angelman syndrome, 20 are associated with a particular electroclinical pattern, which may even be suggestive of a particular diagnosis. Our literature review identified several cases with characteristics in common with the four cases reported here.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 In cases of chromosomal abnormalities, the characteristics of epilepsy are considered to be non-specific, difficult to classify according to the International Classification of Epilepsy, 15 and often resistant to treatment. 16,17 However, some chromosomal abnormalities, such as ring 20 syndrome 18,19 and Angelman syndrome, 20 are associated with a particular electroclinical pattern, which may even be suggestive of a particular diagnosis. Our literature review identified several cases with characteristics in common with the four cases reported here.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 To date no less than 400 different chromosomal imbalances have been associated with seizures or EEG abnormalities consisting in either deletions or duplications. 29 The 8q24 region was previously implicated in different forms of epilepsy (MIM 601068; MIM 603210; MIM 606970; MIM 607876; MIM 600131; MIM 602232; MIM 121201; MIM 138251). The KCNQ3 locus, whose mutations are associated to BFNC (benign familial neonatal convulsions, MIM 121200), lies 10 Mb upstream from the 8q segment duplicated in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Not only do they contribute to chromosomal integrity and to cellular homeostasis, but they also encode several transcripts (12,80). Interestingly, the telomeric regions where the majority of HHV-6 insertions occur are also associated with rare syndromes (e.g., Miller-Dieker syndrome, which is associated with microdeletion and/or LIS-1 gene alteration in chromosome 17p13.3; chromosome 9q subtelomere deletion syndrome; and 18q syndrome, which is associated with an 18q23 deletion [79,[84][85][86]). CIHHV-6 is likely not responsible for these diseases, but the possibility of similar chromosomal alterations caused by HHV-6 integration in these areas is of interest.…”
Section: Cihhv-6-associated Pathologiesmentioning
confidence: 99%